Policy Issues Affecting Lesbian, Gay, Bisexual, and Transgender Families - Cahill, Sean (University of Michigan Press, 2006)
Lesbian, gay, bisexual, and transgender people face the same family issues as their heterosexual counterparts, but that is only the beginning of their struggle. The LGBT community also encounters legal barriers to government recognition of their same-sex relationships and relationships to their own children. Policy Issues Affecting Lesbian, Gay, Bisexual, and Transgender Families addresses partner recognition, parenting, issues affecting children of LGBT parents, health care, discrimination, senior care and elder rights, and equal access to social services. Sean Cahill and Sarah Tobias provide up-to-date, accurate analysis of the major policies affecting LGBT people, their same-sex partners, and their children. This valuable resource offers literature reviews of demographic research as well as original research based on the U.S. Census same-sex couple sample. It also provides a look at the 30-year history of right-wing anti-gay activism and the intra-community intellectual debates over the fight for marriage.